Patients Satisfaction Towards Quality of Nursing Care at a Public Sector Tertiary Care Hospital Karachi : Patients Satisfaction Towards Quality of Nursing Care - Afridi, Tariq; Ali, Amjad; Ali, Afsar; Naz, Subia (Pakistan Journal of Health Sciences, 2024)
Care is seen as a significant element of health amenities. The most anticipated health outcomes are achieved by providing treatments that are effective, efficient, and cost-effective. Objective: To assess the level of patient’s satisfaction towards the quality of nursing care at a public sector tertiary care hospital in Karachi. Methods: This cross-sectional study was accompanied by 312 patients admitted to public sector hospital. Non-probability purposive sampling technique was used for data collection. Those patients who have been admitted for more than three days in various departments. Data were collected after approval Institutional Review Committee (IRC) of the Dow Institute of Nursing and Midwifery (DIONAM) and the Ethical Review Committee (ERC) of the National Institute of Cardiovascular Disease (NICVD). Data were analyzed on SPSS-version 25.0. Frequency and percentage were measured from categorical data. An Independent t-test was run to find out the relationship of patient’s satisfaction and with demographic characteristics of the study participants. Written informed consent was obtained from all participants. Results: The findings highlighted that the majority (55%) of the study participants were male and 79% were married. Furthermore, the highest satisfaction level (90.7) was found in the domain of nurse’s communication, and the lowest level of satisfaction score 81.8% found in the discharge domain. Moreover, the overall patient’s satisfaction score of all domains was 93.3%. Conclusions: The findings of this study concluded that the majority of the admitted patients strongly agreed with the quality of nursing care. Furthermore, the nurse’s communication domain showed a higher level of satisfaction among all domains.